2022
DOI: 10.1111/jocd.15310
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and artificial intelligence: Experts and dermatologists perspective

Abstract: Introduction Artificial intelligence (AI) has an important role to play in future healthcare offerings. Machine learning and artificial neural networks are subsets of AI that refer to the incorporation of human intelligence into computers to think and behave like humans. Objective The objective of this review article is to discuss perspectives on the AI in relation to Coronavirus disease (COVID‐19). Methods Google Scholar and PubMed databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The global reaction to the pandemic was influenced by BlueDot's early warnings to public health personnel about the COVID-19 outbreak that occurred in Wuhan, China, towards the end of 2019. 19 Another AI-driven epidemiological information surveillance system in the United States is called "HealthMap." Based on time, geographic location , and infectious pathogens, it monitors, organizes, and visualizes disease outbreaks.…”
Section: Use Of Ai In Public Healthmentioning
confidence: 99%
“…The global reaction to the pandemic was influenced by BlueDot's early warnings to public health personnel about the COVID-19 outbreak that occurred in Wuhan, China, towards the end of 2019. 19 Another AI-driven epidemiological information surveillance system in the United States is called "HealthMap." Based on time, geographic location , and infectious pathogens, it monitors, organizes, and visualizes disease outbreaks.…”
Section: Use Of Ai In Public Healthmentioning
confidence: 99%
“…In this specific case, it can be observed that the selected reviews did not have the specific task of addressing the development of the integration of TD and AI jointly, which we find were handled as a non-primary sub-research topic. Taking this into account, it is reported that: four reviews addressed the issue by relating it to the impact of the COVID-19 epidemic [42][43][44]46], also with specific reference to some national realities [46]. Some studies have focused on specific pathologies, such as melanoma [47], psoriasis [45], or occupational medicine [54].…”
Section: Data Syntesys Of the Overview Of The Reviewsmentioning
confidence: 99%
“…The role of technological innovation in various sectors of healthcare during the COVID-19 pandemic, including dermatology, was highlighted. The review reported that technology had enabled the sharing and rapid detection of cutaneous signs and symptoms of COVID-19, resulting in reduced face-to-face visits and cost and time savings [44] The development of AI during the COVID-19 pandemic with reference to dermatology was addressed. Research showed that the use of TD and AI was strategic to discern six clinical dermatological patterns with a probable prognostic connection to COVID-19.…”
Section: Data Syntesys Of the Overview Of The Reviewsmentioning
confidence: 99%
“…TH and DH have also been integrated in the use of artificial AI tools in the diagnosis and treatment of COVID-19. Digital radiology, digital pathology, and digital dermatology, as brief examples, have explored new potential in health care [ 49 , 50 , 51 ]. Big Data have played a strategic role in overcoming the pandemic [ 52 ].…”
Section: The Impact Of Covid-19 In This Fieldmentioning
confidence: 99%